Toxicity assessment of superparamagnetic iron oxide nanoparticles in different tissues - Roghayyeh Vakili-Ghartavol; Amir Abbas Momtazi-Borojeni; Zeynab Vakili-Ghartavol; Hammed Tanimowo Aiyelabegan; Mahmoud Reza Jaafari; Seyed Mahdi Rezayat; Sepideh Arbabi Bidgoli (Artificial Cells, Nanomedicine, and Biotechnology, 2020)
Superparamagnetic iron oxide nanoparticles (SPIONs) have been employed in several biomedical applications where they facilitate both diagnostic and therapeutic aims. Although the potential benefits of SPIONs with different surface chemistry and conjugated targeting ligands/proteins are considerable, complicated interactions between these nanoparticles (NPs) and cells leading to toxic impacts could limit their clinical applications. Hence, elevation of our knowledge regarding the SPION-related toxicity is necessary. Here, the present review article will consider current studies and compare the potential toxic effect of SPIONs with or without identical surface chemistries on different cell lines. It centers on cellular and molecular mechanisms underlying toxicity of SPIONs. Likewise, emphasis is being dedicated for toxicity of SPIONs in various cell lines, in vitro and animal models, in vivo.